A rare case of intracranial solitary fibrous tumor that is still alive after multiple surgical resections: a case report and review of the literature - Gao, YiMeng; Xu, Yan; Xie, RuiZhi; Shen, YouBi; Xue, DaoJin; Zhen, Zheng; Lu, JingJing; Huang, Tao; Peng, ZiZhuang (Frontiers in Neurology, 2023)
Solitary fibrous tumor (SFT) is a rare, aggressive, metastasis- and recurrence-prone mesenchymal tumor. We describe a rare instance of SFT that was discovered for the first time intracranially following total surgical removal. The pathology was categorized as HPC at the time by WHO tumor criteria. Imaging review eight months after surgery revealed a tumor recurrence; combined radiation and gamma-knife therapy was continued throughout this time. The tumor didn't spread to the pancreas until 2018, when it did so with ruptured bleeding and postoperative pathology suggestive of SFT. The patient's review in 2020 showed cranial recurrence with systemic metastases. After staged surgical resection and combined multimodality therapy, the patient is still alive almost 3 years after surgery. There is no imaging or clinical evidence of disease recurrence. To our knowledge, there is no previous record of using a combined treatment modality for ISFT. Combined with the patient's experience, we empirically describe a combined approach with a preference for gross-total resection (GTR), supplemented by multimodal assistance with stereotactic (radiotherapy), gamma knife (GK), molecular targeting and immunization, for patients admitted acutely, with accurate preoperative identification and aggressive management after intraoperative case response to maximize treatment of recurrent ISFT and improve prognosis. We believe that this model of care should be considered in the long-term treatment of all malignant recurrent tumors.